2018
DOI: 10.1161/jaha.118.008721
|View full text |Cite
|
Sign up to set email alerts
|

Phase Angle as a Biomarker for Frailty and Postoperative Mortality: The BICS Study

Abstract: BackgroundPhase angle (PA) is a bioimpedance measurement that is determined lean body mass and hydration status. Patients with low PA values are more likely to be frail, sarcopenic, or malnourished. Previous work has shown that low PA predicts adverse outcomes after cardiac surgery, but the effect of PA on survival has not previously been assessed in this setting.Methods and ResultsThe BICS (Bioimpedance in Cardiac Surgery) study recruited 277 patients undergoing major cardiac surgery at 2 university‐affiliate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
60
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 41 publications
7
60
2
4
Order By: Relevance
“…We observed that a PA<5˚ was a sufficient threshold for identifying HNC patients with a shorter median survival. These results correspond to a study of patients undergoing cardiac surgery, where a PA<4.5˚ was indicative for a higher frailty and mortality (19). Another study on palliative care patients suffering mainly from gastric cancer set the PA threshold at <4˚.…”
Section: Discussionsupporting
confidence: 83%
“…We observed that a PA<5˚ was a sufficient threshold for identifying HNC patients with a shorter median survival. These results correspond to a study of patients undergoing cardiac surgery, where a PA<4.5˚ was indicative for a higher frailty and mortality (19). Another study on palliative care patients suffering mainly from gastric cancer set the PA threshold at <4˚.…”
Section: Discussionsupporting
confidence: 83%
“…Generally, a low PhA may suggest deterioration of the cell membrane and cellular dysfunction. A low PhA is associated with frailty [15][16][17] as well as being associated with sarcopenia [18][19][20]. In this study, there was a significant association between the PhA and OH/ECW, but we excluded OH/ECW from the multivariate analysis.…”
Section: Discussionmentioning
confidence: 82%
“…Moreover, low PA was a greater risk factor for frailty even after adjusting for other clinical indicators. Several prior studies have reported an association between low PA and frailty phenomenon in older subjects, 17,18 or cardiac surgery patients, 19 although very few studies have focused on HD patients. 20 In the present study, we also determined that low PA is a representative comprehensive biomarker of malnutrition, frailty, as well as hydration in HD patients.…”
Section: Discussionmentioning
confidence: 99%